2023
DOI: 10.3389/fonc.2023.1275800
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus and B-cell lymphoma: evidence, unmet need, clinical impact, and opportunities

Maya Rosenberg,
Maria Poluch,
Colin Thomas
et al.

Abstract: Nearly a billion people worldwide are infected with the hepatitis B Virus (HBV) and about a third of them have chronic infection. HBV is an important cause of morbidity and mortality, including acute and chronic hepatitis and hepatocellular carcinoma (HCC). Screening and control of primary HBV infection through vaccination represent a major advance in global public health, but large sections of the world population, in both developed and underdeveloped countries, remain unscreened and unvaccinated. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…(16,17) Interestingly, TP73 mutation has been reported in HBV-associated B cell lymphomas but not in T cell lymphomas, despite chronic HBV infection being linked to an increased risk of NK/T cell lymphomas. (18,19) While our patient harbored HBV infection with focal hepatocyte involvement, overall control of the infection was evident. However, T cells did not show signs of HBV infection.…”
Section: Discussionmentioning
confidence: 72%
“…(16,17) Interestingly, TP73 mutation has been reported in HBV-associated B cell lymphomas but not in T cell lymphomas, despite chronic HBV infection being linked to an increased risk of NK/T cell lymphomas. (18,19) While our patient harbored HBV infection with focal hepatocyte involvement, overall control of the infection was evident. However, T cells did not show signs of HBV infection.…”
Section: Discussionmentioning
confidence: 72%
“…This integration is possible due to the reverse transcriptase activity of viral DNA polymerase. The frequency of DLBCL in HBV-infected individuals is increased, and these cases occur primarily in younger adults [ 80 , 81 ]. It has been reported that not only chronic Hepatitis B-infected patients have an increased likelihood of developing DLBCL, but individuals who underwent HBV infection and fully recovered have an increased risk of B-cell lymphoma development as well.…”
Section: Viral Infectionsmentioning
confidence: 99%
“…( 101 ) When infection occurs, the host may experience acute infection with full recovery, or chronic infection or an acute course leading to hepatic failure. ( 102 ) The relationship between HBV infection and NHL has been explored ( 103 105 ). However, HBsAg + is not associated with elevated risk of HL, multiple myeloma (MM), or various types of leukemia ( 106 ).…”
Section: Hepatitis B Virusmentioning
confidence: 99%